THE RELATIONSHIP BETWEEN VUCA AND EMPLOYEE COMPETENCIES IN MALAYSIA BANKING SECTORS: THE MEDIATING ROLE OF EMOTIONAL INTELLIGENCE - Sani, Rozaini; Ahmad, Nursaadatun Nisak; Zaman, Maliza Delima Kamarul; Che Yahya, Norliza (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
Employees in the Malaysian banking sector increasingly operate in a VUCA environment characterised by volatility, uncertainty, complexity, and ambiguity. While employee competencies are essential for performance, they may be insufficient on their own when employees face rapid change, unclear outcomes, and intensified workplace demands. This research examines the relationship between VUCA elements and employee competencies and investigates emotional intelligence as a mediating mechanism that may strengthen employees’ adaptability and performance under such conditions. Grounded in McClelland’s Competency Model and Mayer and Salovey’s Emotional Intelligence theory, this research adopts a quantitative design using questionnaire data collected from full-time banking employees in the Klang Valley. Respondents are aged 21 years and above and have at least one year of work experience. The research highlights the practical importance of integrating competency development with emotional intelligence enhancement to support resilience, teamwork, and leadership in challenging environments. The findings offer implications for human resource practices, particularly in recruitment, performance management, and employee development initiatives. By strengthening both competencies and emotional intelligence, banking institutions can enhance workforce readiness and better respond to emerging challenges and opportunities in a VUCA context.